2020
DOI: 10.2903/j.efsa.2020.6167
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the application for renewal of the authorisation of Actisaf® Sc 47 (Saccharomyces cerevisiae CNCM I‐4407) as a feed additive for calves for rearing

Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed ( FEEDAP ) was asked to deliver a scientific opinion on the assessment of the application for renewal of authorisation of Actisaf ® Sc 47 ( Saccharomyces cerevisiae CNCM I‐4407) as a zootechnical additive for calves for rearing. The applicant has provided evidence that the additive currently in the market compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In its previous opinions, the FEEDAP Panel concluded that, following the qualified presumption of safety (QPS) approach to the safety assessment, S. cerevisiae CNCM I‐4407 is safe for the target species, consumers and the environment (EFSA FEEDAP Panel, 2012 , 2020 ). The safety for the user was evaluated by EFSA FEEDAP Panel in previous assessments (EFSA FEEDAP Panel, 2012 , 2018a , 2019 , 2020 ). The FEEDAP Panel concluded that Actisaf® Sc 47 in any form is not a skin or eye irritant and no conclusions could be drawn on the dermal sensitisation potential of the additive.…”
Section: Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In its previous opinions, the FEEDAP Panel concluded that, following the qualified presumption of safety (QPS) approach to the safety assessment, S. cerevisiae CNCM I‐4407 is safe for the target species, consumers and the environment (EFSA FEEDAP Panel, 2012 , 2020 ). The safety for the user was evaluated by EFSA FEEDAP Panel in previous assessments (EFSA FEEDAP Panel, 2012 , 2018a , 2019 , 2020 ). The FEEDAP Panel concluded that Actisaf® Sc 47 in any form is not a skin or eye irritant and no conclusions could be drawn on the dermal sensitisation potential of the additive.…”
Section: Assessmentmentioning
confidence: 99%
“…In previous assessments for the renewal of the authorisation of the additive, two literature searches on the safety of the product covering the periods 2007–2016 (EFSA FEEDAP Panel, 2018a ) and 2016–2019 (EFSA FEEDAP Panel, 2020 ) were evaluated by the FEEDAP Panel. These searches did not reveal any safety issue related to the additive under assessment.…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…EFSA issued several opinions on the safety and efficacy of this additive (EFSA, 2006a , 2006b , 2006c , 2007a , 2007b , 2008 , 2010 ; EFSA FEEDAP Panel, 2012 , 2018a , 2018b , 2019 , 2020 ).…”
Section: Introductionmentioning
confidence: 99%